STRATEGI BADAN PELAYANAN PAJAK DAERAH KOTA MALANG DALAM MENGURAI TUNGGAKAN PAJAK BUMI BANGUNAN (PBB) - M. N. Romi A.S; Dewi Citra Larasati (Universitas Tribhuwana Tunggadewi, 2018)
Land and Building in Indonesia are worned taxes regional. This tax as called PBB is one of the taxes transferred from the Central Government to the Local Government. The government of Malang City has made program of PBB at the beginning of the year in 2013. Authority about PBB are delegated to institution BP2D. BP2D are affording receivable amount Rp.110.348.875.252,- from PBB. The researcher has interestingabout strategic this institution to increase income from PBB. This research use desciptive qualitative approach. The outcome from this research are 1) BP2D often held a tax socialization, 2) The institution cooperating with stakeholders, 3) BP2D were establisinga unit to enforce taxes. This unit as called OPGAB, 5) The official are mapping about economic ability, 6) Implementation of a program was called Sunset Policy, 7) operate the tax car, and 8) Institution giving rewards totaxpayers who have good payment.